Spread of Agriculture of Critical Land using Land Evaluation Framework Approach in Welang Watersheed, Indonesia - Maroeto; Suntoro W.A; Joko Suyono; Rossyda Priyadarshini (Nusantara Science and Technology Proceedings)
Land degradation has become a global issue of the world, which leads to critical land conditions. If the distribution of critical land agriculture can be known, it will make it easier to formulate sustainable land use. This research was conducted in Welang Watershed, Pasuruan. The data attribute table of some combination of the results of the evaluation parameters of the land evaluation. In general, constraints on land criticality are identified as redox value and high number of microbes as the dominant parameter of land damage standard. In units of vegetable garden use for various uses such as for the cultivation of cabbage, potatoes and carrots, while mixed gardens on land criticality have a class of ability III for uncritical land and a critical potential to be somewhat critical of having an IV capability class, with annual crops for example coffee, cloves and durian. The classification of soil fertility capabilities in the vegetable garden land use unit as a whole has a high cation exchange capacity. Assessment of land suitability on the condition of vegetable garden and mixed garden land at various level of land criticality and adjusting to the desire of the farmer appears for vegetable crop only cabbage, potato and carrot for which farmers want while for plant mixture of coffee, clove and durian which appear in highland region . Farmer awareness and government intervention are expected to improve farmers' living standards from the agricultural sector while maintaining sustainable land for sustainable agriculture.